'A wolf in sheep's clothing': settler voting rights and the elimination of the Indigenous demos in US Pacific territories. Issue 2 (3rd April 2019) - Spitzer, Aaron John
ABSTRACT: Settler colonialism eliminates Indigenous sovereignty, enthrones itself, and thereby makes Indigenous land 'ours'. It may do this meta-politically, by absorbing 'them' into 'us'. This article explores three recent lawsuits brought by settlers against Indigenous demoi in US Pacific territories. I show that in each lawsuit, settlers brandished a novel 'tool of elimination': individual voting rights. I trace how settlers wielded this tool to deliver a 'one-two punch', first condemning as 'illiberal' restrictive voting laws flowing from Indigenous sovereignty and then championing race-neutral laws that would in effect enthrone settlers. I show that courts hearing these cases were faced with choosing the appropriate 'framing of justice' – with whether the relevant rights-bearer was the universal individual voter or the 'constitutionally prior' Indigenous demos. Finally, I show that, because the courts ultimately framed these disputes as individual-rights cases, settlers extended control of meta-politics on the US Pacific frontier.